Measuring the success of UTM e-learning system based on Delone and Mclean's information systems success model - Talebi, Amir (2010)
Today, information systems applications can be seen in a broad range in any organization. Academic environments like other organizations have been using information systems applications too. The majority of processes are done by means of IS related applications to save time and cost and also to provide the students with better services. One of them is E-Learning system which can have a big influence on the way the students and lecturers learn and teach, but this will not happen unless the application is effective and efficient. Thus, in this project, the researcher evaluates the success of E-Learning as an information system application in Universiti Teknologi Malaysia. To achieve the objectives of the project, finding the appropriate factors of success was the first and the most important step. Next, by comparing various models of information systems success, the researcher chose Delone and Mclean’s Updated Model of Information Systems Success as a tool to measure the factors. By conducting a survey and analyzing the results using SPSS software, the researcher finalized the project successfully.